ENGLISH TEACHERS’ PERCEPTIONS TOWARDS THE IMPLEMENTATION OF “KURIKULUM MERDEKA” AT SMA ASSA’ADAH BUNGAH GRESIK - Wardani, Happy Kusuma; Fanani, M. Aji Tamam; Hidayah, Bariqotul (STKIP PGRI Jombang, 2024)
This research aims to explore the English teachers' perceptions concerning ‘Kurikulum Merdeka’ within the English subject at SMA Assa’adah Bungah, Gresik. Employing a descriptive qualitative approach, this research used questionnaires as an instrument for collecting the data. The research unveils English teachers' perceptions towards the implementation of ‘Kurikulum Merdeka’ at SMA Assa’adah including the general concept of 'Kurikulum Merdeka,' Project-Based Learning, teaching modules, and assessment. The findings exhibit an overall positive perception among teachers. They appreciate the curriculum's focus on students’ independence, character development, and diverse assessment methods.